Young People’s Safety Practices when Drink Walking in the Suburbs of Manchester, UK - Уилкинсон, Саманта; Уилкинсон, Катрин (Научни трудове, 2019)
Walking whilst intoxicated is a high-risk activity; it is thus important to enhance understandings of young people’s experiences of walking, bound up with the consumption of alcohol. In this paper, we argue that ‘mobilities’ theory has potential to enhance understandings of the emotional, embodied and affective aspects of young people’s alcohol related journeys. This paper draws on innovative qualitative research, comprising: individual and friendship group interviews and peer interviews, conducted with 40 young people, aged 15-24, living in the suburban case study locations of Chorlton and Wythenshawe, Manchester, UK. When young people’s alcohol-related mobilities have been considered, for instance in the transport studies literature, it has typically been conceptualised in a reductive manner which theorises mobility as “a product of rationally weighed decisions” (Spinney, 2009:820). We join a small body of work, in highlighting the emotional, embodied and affective aspects of alcohol-related mobilities. This paper presents findings around two main themes: performing walking and safety, and forced and adaptive mobilities, respectively. This paper concludes by recommending ways to improve the safety of young people’s walking practices when on nights out involving alcohol.